Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis screening and treatment of pregnant women in Port-au-Prince, Haiti. (October 2017) - Bristow, Claire C; Mathelier, Patricia; Ocheretina, Oksana; Benoit, Daphne; Pape, Jean W; Wynn, Adriane; Klausner, Jeffrey D
In Haiti, routine screening for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Trichomonas vaginalis (TV) among pregnant women is not conducted; yet these sexually transmitted infections (STIs) are associated with adverse birth and newborn health outcomes. We aimed to assess the acceptability and feasibility of screening and the prevalence of STIs among pregnant women in Port-au-Prince, Haiti. Pregnant women of at least 18 years of age who attend Haitian Study Group for Kaposi's sarcoma and Opportunistic Infections (GHESKIO) clinics in Port-au-Prince, Haiti provided self-collected vaginal swab specimens. Laboratory testing was done with Xpert® CT/NG and Xpert® TV. The results of this study showed that of the 322 pregnant women who visited GHESKIO for their regular scheduled appointments, 300 (93.2%) consented for CT, NG, and TV testing. Of those, 107 women (35.7%) tested positive for at least one STI. There were 42 (14.7%) cases of CT, 8 (2.8%) NG, and 83 (29.0%) TV infections. Most infections were treated – 122 of 133 (91.7%). In summary, we found that it was highly acceptable and feasible to implement CT, NG, and TV screening among pregnant women in Port-au-Prince, Haiti. We found high prevalence of STIs among pregnant women, which suggest that STI screening in this population may be warranted.